Random error propagation on electron beam dynamics for a 50 MeV S-band linac. (1st February 2023) - Purwar, H; Goutierre, E; Guler, H; Rossetti Conti, M; Chance, S; Gonnin, A; Monard, H; Bacci, A; Sebag, M; Cohen, J; Bruni, C
Abstract: The stability and the quality of particle beams are of utmost importance for many emerging linac installations. The impact on beam properties damage of beam electromagnetic element misalignments and jitter/fluctuations in various accelerator sub-systems should be properly known, as usually such shot-to-shot fluctuations cannot be avoided. On top of that, knowing which parameters the machine is most sensitive to is of utmost to take precautionary measures to reduce the beam degradation and thus improve beam stability and quality. This simulation work focuses on a 50 MeV S-band linear accelerator based on RF photoinjector electron source. The sensitivity of the beam parameters towards several errors has been studied collectively as well as individually for each accelerator element. While the emittance at the end of the linac is dominated by the laminar behavior in the accelerating section, the main emittance degradation comes mainly from orbit errors located at the linac entrance.